Investigation by confocal Raman microspectroscopy of the molecular factors responsible for grain cohesion in the Triticum aestivum bread wheat. Role of the cell walls in the starchy endosperm - PIOT, O; AUTRAN, J.-C; MANFAIT, M (Journal of cereal science, 2001)
Confocal Raman microspectroscopy has previously been employed to investigate the protein content and composition of the starchy endosperm of the wheat grain. With the same objective, that is to determine the molecular basis of grain cohesion and more specifically of kernel hardness, the contribution of endosperm cell walls in the kernel structure and cohesion was explored. The technique showed that endosperm cell walls consist not only of arabinoxylan chains with ramifications of ferulic esters, but also of others components such as proteins and lipids that could play some role in the mechanical properties of the endosperm cell walls. A new model of interaction between ferulic ramifications and a phospholipid component was proposed. The investigation of cell wall composition at successive stages of grain development revealed a decrease in the protein to arabinoxylan ratio and simultaneously an increase of the ferulic acid to arabinoxylan ratio that could be associated with a strengthening of the cell wall structure. The study confirms the effectiveness of confocal Raman microspectroscopy to approach the structure of wheat grain at the micrometer scale and to identify specific molecular factors responsible for grain cohesion and involved in the fracture modes generated during the milling process.